Number of Metabolic Syndrome Risk Factors is Related to Carotid Intima-Media Thickness in Rheumatoid Arthritis Patients - Ferhat GÖKMEN,; Ahmet TEMİZ,; Ayla AKBAL,; Hacer ŞEN,; Coşkun ZATERİ,; Esra GÖKMEN,; Emre BOZKURT,; Hatice REŞORLU,; Tolga KURT,; Yılmaz SAVAŞ, (Archives of Rheumatology, 2015)
Objectives: This study aims to investigate the relationship between carotid intima-media thickness (CIMT) and clinical and metabolic variables in rheumatoid arthritis (RA) patients. Patients and methods: The study included 76 RA patients (18 males, 58 females; mean age 50.1±9.8 years; range 21 to 69 years) and 42 control subjects (11 males, 31 females; mean age 49.2±9.7; range 28 to 66 years). Erythrocyte sedimentation rate, C-reactive protein, and disease activity score were used to assess disease activation. Rheumatoid factor, anti-cyclic citrullinated peptide antibodies, and metabolic syndrome components (fasting blood glucose, high density lipoprotein-cholesterol, triglyceride, blood pressure, and waist circumference) were measured. Results: Mean disease duration was 6.9±6.5 years. Patients with RA had higher CIMT than the controls (0.8±0.1 and 0.6±0.2, respectively; p<0.001). Statistically significant positive correlations were observed between CIMT and age, erythrocyte sedimentation rate, C-reactive protein, and systolic and diastolic blood pressure. The CIMT in RA patients having metabolic syndrome risk components ranging from one to four were 0.76±0.16, 0.82±0.14, 0.86±0.13, and 0.92±0.13, respectively. CIMT was positively correlated with the number of metabolic syndrome risk components. Conclusion: Our study has shown elevated CIMT in RA. Presence of metabolic syndrome components in RA patients increases tendency to atherosclerosis and constitutes a severe risk for cardiovascular disease.